1965
DOI: 10.1111/j.1749-6632.1965.tb49416.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Dynamics in the Ox and Giraffe, With Comparative Observations on Man and Other Mammals*

Abstract: Comparative mammalian physiology not only is important as an intellectual discipline in its own right, but it also provides a perspective which can contribute to the understanding of physiological processes in a given species.As an example, those functions of the organism which appear related to body weight or to body surface area can be studied over a wide range of animal size, providing more extensive data for the precise analysis of relationships than could be obtained from investigations confined to member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 18 publications
1
25
1
Order By: Relevance
“…What can be measured is Resting Metabolic Rate (RMR; mlO 2 /kg. min -1 ) and it has been measured twice in giraffes (Patterson et al, 1965;Langman et al, 1982). Their results differ widely.…”
Section: Resultsmentioning
confidence: 99%
“…What can be measured is Resting Metabolic Rate (RMR; mlO 2 /kg. min -1 ) and it has been measured twice in giraffes (Patterson et al, 1965;Langman et al, 1982). Their results differ widely.…”
Section: Resultsmentioning
confidence: 99%
“…After making measurements of giraffe blood pressure Goetz and Keen concluded that the giraffe cranial circulation proceeded unassisted by siphons or peristalsis although it was 'doubtless aided by subatmospheric pressures at the brain level' . Goetz and colleagues Warren et al, 1957) later concluded, however, that there was no 'necessity for any important contribution to cerebral perfusion pressure from negative venous pressure at brain level' (Patterson et al, 1965). If a siphon does exist then the origin of arterial blood pressure suggested by Badeer (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(Patterson et al, 1957) and (Patterson et al, 1965) compared giraffe and cow respiratory characteristics and also found a large dead space volume in giraffes (2.6 mL/kg vs 1.0 mL/kg in cows), a lung mass of the expected 1% of body mass but a "surprisingly small lung volume", and a higher respiratory rate. Inspiration time was prolonged compared to cows (ca 2 to 3 s vs 0.9 s respectively), expiration time was similar (1.62 s vs 1.67 s) and the average ratio of inspiration time to expiration time was 1.2 in giraffes and 0.6 in cows (Patterson et al, 1965). Conversely, Hugh-Jones et al (1978) found that while giraffe dead space was ca 3 mL kg −1 , it was 3.6 in deer (Cervus elephas), 3.1 in Llama (Lama glama) and 1.8 in camels (Camelus dromedarius), and thus was not unusually large.…”
Section: Introductionmentioning
confidence: 98%
“…Robin et al (1960) concluded that to overcome the large dead space the lungs were disproportionately larger and respiratory rate lower (8-10 bpm) than expected for similar-sized animals. (Patterson et al, 1957) and (Patterson et al, 1965) compared giraffe and cow respiratory characteristics and also found a large dead space volume in giraffes (2.6 mL/kg vs 1.0 mL/kg in cows), a lung mass of the expected 1% of body mass but a "surprisingly small lung volume", and a higher respiratory rate. Inspiration time was prolonged compared to cows (ca 2 to 3 s vs 0.9 s respectively), expiration time was similar (1.62 s vs 1.67 s) and the average ratio of inspiration time to expiration time was 1.2 in giraffes and 0.6 in cows (Patterson et al, 1965).…”
Section: Introductionmentioning
confidence: 99%